Game on! Burning issues in game localisation - Mangiron, Carme (Journal of Audiovisual Translation, 2018)
Game localisation is a type of audiovisual translation that has gradually been gathering scholarly attention since the mid-2000s, mainly due to the increasing and ubiquitous presence of video games in the digital society and the gaming industry's need to localise content in order to access global markets. This paper will focus on burning issues in this field, that is, issues that require specific attention, from an industry and/or an academic perspective. These include the position of game localisation within the wider translation studies framework, the relationship between game localisation and audiovisual translation, game accessibility, reception studies, translation quality, collaborative translation, technology, and translator training.